Does accounting information contribute to a better understanding of public assets management? The case of local government infrastructural assets. Issue 2 (17th February 2021) - Ehalaiye, Dimu; Redmayne, Nives Botica; Laswad, Fawzi
ABSTRACT: The authors examine whether the publicly-available accounting information about infrastructural assets and other information in New Zealand local government's financial statements is helpful for the assessment of investment in infrastructural assets. Their analysis indicates that information on annual net investments for infrastructural assets is useful for understanding the level and type of infrastructural assets investments and how these assets are funded. Further, such investment focuses more on visible infrastructural assets than invisible infrastructural assets. This study contributes to the literature on the reporting and management of public infrastructure assets. IMPACT: Local government in many countries is responsible for investing and maintaining infrastructural assets and is often accused of under-investing in these assets. Information published in local government financial statements can assist in assessing the level of funding sources for infrastructural assets and the choices that local government makes in relation to which types of assets are funded. This paper's finding that local government allocates more funding to visible, rather than invisible, infrastructural assets has important policy implications for the sustainability of invisible infrastructural assets and will be of interest to both local and central governments.